Novel and Practical Method to Quantify the Quality of Mobility: Mobility Energy Productivity Metric. Issue 10 (October 2019) - Hou, Yi; Garikapati, Venu; Nag, Ambarish; Young, Stanley E.; Grushka, Tom
Recent technology innovations are enabling fundamental improvements in mobility systems, including options for new travel modes, methods, and opportunities to connect people with goods, services, and employment. A desire to quantify and compare both existing and emerging transportation options motivated development of the mobility energy productivity (MEP) metric described here. The MEP metric fundamentally measures the potential of a city's transportation system to connect a person to a variety of services and activities that define a high quality of life, relative to the convenience, cost, and energy needed to provide these connections. Fundamentally derived from accessibility theory, the MEP advances practice by using readily available travel time data (either from web-based application programming interfaces or outputs from an urban transportation model) combined with established parameters that reflect the energy intensity and cost of various travel modes, and relative frequency of activity engagement. The construction of the MEP metric allows for aggregation and disaggregation to the appropriate spatial, modal, and trip purpose resolution, as analysis needs dictate. The MEP could be used to compare alternative futures related to technology, infrastructure investment, or policy, providing a much-needed tool for planners, researchers, and analysts.